2017
DOI: 10.1111/jcpp.12826
|View full text |Cite
|
Sign up to set email alerts
|

Impact of extremely low‐birth‐weight status on risk and resilience for depression and anxiety in adulthood

Abstract: Extremely low-birth-weight survivors may be more sensitive to traditional risk factors for psychopathology and less protected by resiliency factors. Intervention strategies aimed at preventing or reducing exposure to traditional childhood risk factors for psychopathology may reduce the burden of mental illness in adult survivors of prematurity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
19
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 30 publications
(23 citation statements)
references
References 44 publications
4
19
0
Order By: Relevance
“…A recent body of research suggests that lower BW is associated with a variety of diseases of adulthood, including cardiovascular diseases, diabetes, hypertension, and other metabolic disorders (Godfrey & Barker, ). Additionally, low BW has been associated with potential risk for depression and anxiety in adulthood (Van Lieshout et al, ), increased fracture risk (Balasuriya et al, ), and neurodevelopmental difficulties including Attention Deficit Hyperactivity disorder (Momany, Kamradt, & Nikolas, ), among other health‐related conditions.…”
Section: Introductionmentioning
confidence: 99%
“…A recent body of research suggests that lower BW is associated with a variety of diseases of adulthood, including cardiovascular diseases, diabetes, hypertension, and other metabolic disorders (Godfrey & Barker, ). Additionally, low BW has been associated with potential risk for depression and anxiety in adulthood (Van Lieshout et al, ), increased fracture risk (Balasuriya et al, ), and neurodevelopmental difficulties including Attention Deficit Hyperactivity disorder (Momany, Kamradt, & Nikolas, ), among other health‐related conditions.…”
Section: Introductionmentioning
confidence: 99%
“…Yet their unfavorable consequences might be huge and nonnegligible and continuing for lifelong. Lots of studies have shown that preterm births are under greater risks of neurodevelopmental impairments (such as mental retardation and cerebral palsy), behavioral sequelae (such as dysfunction in cognitive areas) and other problems like hospital readmissions [24]; LBW newborns are at an increased risk of the development of coronary heart disease [25], depression and anxiety [26], poor long-term consequences on lung functions [6], diabetes, blood pressure and neurological functions in later life [27]; macrosomia infants are at elevated shortterm risks like shoulder dystocia and long-term risks of metabolic syndrome, asthma and even cancer [28]. What's more, prematurity-associated complications and macrosomia are proven to be closely related to neonatal deaths and both fetal growth restriction and preterm births are strongly associated with placental dysfunction and subsequent poor fetal health, carrying increased risks of stillbirths [9,17,23].…”
Section: Discussionmentioning
confidence: 99%
“…VLBW subjects in the present study were comparable to the controls in major family and socio‐economic factors. Resiliency factors are likely to contribute towards a neutralisation of unfavourable biological factors associated with preterm birth . In addition, a study published in 2018 has shown that grey matter alterations between adolescence and adulthood were suggested to be related to a maturation of the brain .…”
Section: Discussionmentioning
confidence: 99%